Mobile Banking Service Quality and Customer Retention: A Moderated Mediation Model of Customer Perceived Value and Perceived Corporate Image - Kipkirui Langat, Daniel; Bonuke, Ronald; Kibet, Yusuf (SEISENSE Journal of Management, 2021)
Purpose- This study examined the moderating effect of perceived corporate image on the indirect relationship between mobile banking service quality and customer retention via customer perceived value in the Kenyan banking industry Design/Methodology- The study adopted an explanatory research design, employing multistage, simple random and systematic sampling techniques in collecting data from a sample size of 400 consumers of mobile banking services in Kenya using a self-administered questionnaire Findings- The results reveal a significant mediating effect of customer perceived value on the relationship between mobile banking service quality and customer retention. Moreover, the study established that perceived corporate image moderates the relationship between; mobile banking service quality and customer perceived value and mobile banking service quality and customer retention. Finally, perceived corporate image moderates the indirect link between mobile banking service quality and customer retention via customer retention at all levels Practical Implications- These findings underscore the need for the bank’s management and policymakers to develop quality assurance policies and devise value-centered strategies and image-enhancing strategies to enhance customer retention. Originality/Value - The study’s findings bring new critical knowledge concerning the indirect effect of customer perceived value and perceived corporate image on the study variables.